Can Contingent Convertibles Help Private Asset Managers Fund Their Acquisition of Non-Performing Loans from Portuguese Banks? - Santos, Andre (IMF Working Papers; Working Paper ;, 2019)
This paper analyzes the capital structure of private asset managers in which the acquisition of nonperforming loans (NPLs) is funded with Contingent Convertibles (CoCos) placed with investors. The paper develops a model based on NPL transfer prices and residual recovery rates to assess capital structures consisting of CoCos and equity. The CoCos would contain put and call options to write down losses and write up profits, respectively, arising from liquidation and restructuring procedures. The paper concludes that the protection mechanism provided by debt write-downs embedded in CoCos and the incentives to investors provided by debt write-ups could help bridge the gap between Portuguese banks' NPL bid prices and private equity firms' ask prices.